La reforma judicial de 1994 en México - González-gómez, Gabriela Beatriz; González Chávez, Ma. De Lourdes (Nómadas. Critical Journal of Social and Juridical Sciences, 2007)
The article comprises of the theoretical foundation of the doctoral investigation that was carried out in the Independent University of the State of Mexico on the impact of social factors in the performance of the personnel of the Judicial Power that consequently caused the federal constitutional reform of 1994 when modifying the structure and operation of the Supreme Court of Justice and, of all the Judicial Power of Mexico. The text developed here approaches the most general principles of the theory of justice of John Rawls, theory of the feelings of Agnes Heller and the Scandinavian sociological realism of Alf Ross in order to resist them with the theoretical sustenance of the main consultants of the World Bank who elaborated the Programs of reforms in the judicial scope which they were carried out in greater or smaller